Assessment of depression, anxiety and stress among patients with type II diabetes mellitus attending a tertiary care centre - Hazarika, Kasturi; Ali, M. Fahad; Agarwal, Saurabh; Verma, Shivendra; Singh, Vipul (International Journal of Advances in Medicine, 2023)
Background: India is home to 17% diabetic ( 80 million) population of world and is expected to increase to 135 million by 2045. Chronic illnesses association with psychiatric morbidity. Positive relationship exists between diabetes and psychiatric disorders and have definite negative impact on self-care practices, worsening physical and mental health, diminishing quality of life (QoL) and poor resulting in greater economic burden both to family and society. Method: A cross-sectional study was conducted in a diabetes clinic of a tertiary care facility in North India. Hindi version of DASS 21 was used to ascertain the psychological health of patients which determine the presence of depression, anxiety and stress. Data were analysed using SPSS 20.0 Results: We found a high prevalence of depression (49.7%), anxiety (69.7%) and stress (68.3%) among patients belonging to lower socioeconomic status, rural residence and lower literacy rates/illiteracy. The prevalence of depression was higher among females. Conclusions: There is a high prevalence of psychiatric morbidity among the North Indian diabetic population which shows some variability with changing demographic profile.